2002
DOI: 10.4319/lo.2002.47.1.0230
|View full text |Cite
|
Sign up to set email alerts
|

The rates and pathways of carbon oxidation in bioturbated saltmarsh sediments

Abstract: This study was carried out to quantify the effects of higher organisms, invertebrate macrofauna, and macrophyte plants on the rates and pathways of microbial respiration coupled to organic matter oxidation in saltmarsh sediments. Sediment geochemistry, rates of microbial metabolism, and the abundance of anaerobic respiratory bacteria were determined at sites differing in the abundance of fiddler crab (Uca pugnax) burrows and vegetation (Spartina alterniflora) coverage. Solid-phase Fe(III) concentrations were 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
137
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(158 citation statements)
references
References 36 publications
19
137
0
2
Order By: Relevance
“…Although it has been known that burrowing organisms affect sediment biogeochemistry, the interactions are often complex and detailed investigations on the effect of geochemical microzonations on microbial diversity are scarce (Kostka et al, 2002;Lucas et al, 2003;Matsui et al, 2004;Papaspyrou et al, 2006). This is not surprising because studies on microbial diversity in marine sediments have also only just begun (Mu mann et al, 2005;Wilms et al, 2006;Wu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been known that burrowing organisms affect sediment biogeochemistry, the interactions are often complex and detailed investigations on the effect of geochemical microzonations on microbial diversity are scarce (Kostka et al, 2002;Lucas et al, 2003;Matsui et al, 2004;Papaspyrou et al, 2006). This is not surprising because studies on microbial diversity in marine sediments have also only just begun (Mu mann et al, 2005;Wilms et al, 2006;Wu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Their burrows have been acknowledged as important conduits for chemical exchange between the water column and the sediment, linking the activity of these crustaceans to nutrient recycling, organic matter degradation and primary productivity (for example, Kostka et al, 2002;Papaspyrou et al, 2005). In this study, we examined the impact of the bioturbation activity of the ghost shrimp Neotrypaea californiensis and the fiddler crab Uca crenulata on microbial community compositions in the sediment.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial Fe reduction has been quantified directly in sediments of various coastal oceans (Gribsholt et al, 2003;Kostka et al, 2002a, b;Hyun et al, 2007Hyun et al, , 2009b and indirectly in deeper continental margins (Thamdrup and Canfield, 1996;Jensen et al, 2003;Kostka et al, 1999). Earlier estimation from 16 different continental margin sediments indicated that Fe(III) reduction contributed 22 % on average to anaerobic carbon oxidation .…”
Section: Org Oxidation Dominated By Manganese Reduction In the Ubmentioning
confidence: 99%
“…However, in sediments where manganese and iron oxides are abundant or rapidly recycled, microbial reduction of manganese and iron can be the dominant electron-accepting processes over sulfate reduction (Sørensen and Jørgensen, 1987;Aller, 1990;Canfield et al, 1993b). The significance of dissimilatory iron reduction for C org oxidation is well established in the sediments of various continental margins and coastal wetlands Thamdrup and Canfield, 1996;Jensen et al, 2003;Kostka et al, 2002a, b;Vandieken et al, 2006;Hyun et al, 2007Hyun et al, , 2009b. However, only a few locations such as the Panama Basin (Aller, 1990), the coastal Norwegian trough in Skagerrak and an adjacent fjord (Canfield et al, 1993a, b;Vandieken et al, 2014), the Black Sea shelf , and the continental shelf of the northern Barents Sea (Vandieken et al, 2006;Nickel et al, 2008) are known where microbial manganese reduction significantly contributes to carbon mineralization.…”
mentioning
confidence: 99%
“…Yet, Fe(III)-reducing bacteria are abundant in marine soils and sediments (Lowe et al, 2000;Kostka et al, 2002c), and several workers have noted that Fe(II) continues to accumulate when H 2 S production is blocked by molybdate, apparently because of enzymatic Fe(III) reduction (Canfield, 1989;Canfield et al, 1993b;Mines et al, 1997;Jacobson, 1994;Joye et al, 1996;Kostka et al, 2002c;S0rensen, 1982).…”
Section: Abiotic Versus Biotic Reductionmentioning
confidence: 99%